Impact of Conflict Induced Displacement on Primary and Secondary Schooling in Pakistan: An Empirical Analysis - Anayat Ullah; Syed Hasnain Ali Abbas; Faryal Shah; Muneer Khan Orakzai (International Journal of Community Service & Engagement, 2021)
Abstract The impact of armed conflict on primary and secondary schooling is very hazardous and apparent. Since, 2001 the conflict has made millions of people displaced in the form of Internally Displaced Persons (IDPs) mainly from Tribal Areas on western border with Afghanistan to the settled areas within Pakistan. This research addressed the impact of internal conflict on primary and secondary level school children during displacement at Jalozia camp, Khyber Pukhtoonkhwa. For that reason, the household survey was conducted at Jalozai IDPs camp. The survey results indicate that conflict induced displacement has negatively impacted the level of schooling both at primary and secondary level. However, the impact is more hazardous for secondary schooling. Due to some socio-economic and cultural constraints, mostly female students were dropout of schools at secondary kevel. In addition, conflict affected the socio-economic status of the marginalized displaced people which either way affected the schooling of displaced children. Key words: Conflict; Displacement; Schooling; Socio-Economic Status; Pakistan